Changing the interfacial composition of carbide precipitates in metals and its effect on hydrogen trapping. (February 2019) - Kirchheim, Reiner
Abstract: Hydrogen trapping at metal/carbide interfaces is changed with changing interfacial composition. This has been exemplified for the iron/vanadium carbide (VC) interface. It will be assumed that the carbide interface is a (100)-plane having a composition between the limiting cases of either 50% V and 50% C for excess carbon in iron or 50% V and 50% carbon-vacancies for excess vanadium in iron. The latter will provide strong traps for hydrogen. For validating the simple model a modified interpretation of published atom probe and thermal desorption data became necessary as discussed in the present work. Graphical abstract: